GAMBARAN DISENFRANCHISED GRIEF (STUDI PADA PEREMPUAN YANG MELAKUKAN ABORSI KARENA HAMIL DI LUAR NIKAH) - Mungil Rheinnita; Wieka Dyah Partasari (MANASA, 2012)
Abortion or pregnancy termination is a difficult choice some women have to make when they become pregnant out-of-wedlock. This situation is usually faced by young women who are not yet ready to get married or to take care of their children due to several conditions, such as the fact that they are still in school, their partners are unemployed, or are still depending on their own parents. The psychological effects of abortion include feelings of loss and grief, but it’s often difficult for these women to express their feelings of grief. Many times, they also experiencing lack of sympathy and support from the people closest to them. This condition is called disenfranchised grief This qualitative study aims to provide a description of disenfranchised grief and its affecting factors. The research involved two subjects who were interviewed using a general interview guideline. Subjects characteristics are: having an induced abortion within the past year, and said abortion was not done due to a medical condition. The first subject hadtwo abortions. Both subjects had their abortions at medical clinics and/or hospitals with medical assistance. During the abortion procedure, they were accompanied by their parents and boyfriends. Both subjects were found to experience disenfranchised grief. They have shown symptoms such as feeling ashamed and worthless, guilt, anger, selfdisenfranchisement, having destructive behavior such as getting drunk, promiscuous sexual behavior, repeated abortions and conflicts with people associated with the abortion. Family, boyfriends and friends, as well as personality traits/characteristics were found to be factors that influence disenfranchised grief, both in a positive or a negative way. Religious and cultural rituals were found to be factors that help easing grief. Further research should focus on disenfranchised grief in parents and partners, as well as further exploration of factors affecting similar phenomenon.